Mapping Freshwater Carbonate Deposits by Using Ground-Penetrating Radar at Lake Kolon, Hungary - Pécsi, Eszter; Katona, Orsolya; Barta, Károly; Sipos, György; Biró, Csaba (Journal of Environmental Geography, 2014)
Freshwater carbonate deposit, as a special phenomenon in the Danube-Tisza Interfluve, located in the centre of Hungary, is a significant geological heritage in the Carpathian Basin. At present there is not any applicable method to investigate the presence of carbonate layers in an undisturbed way, as neither vegetation nor morphological characteristics indicate unambiguously these formations. Ground-penetrating radar technology is widely used in various earth science related researches, and the number of applications is steadily increasing. The aim of the study was to determine the spatial extension of freshwater limestone using geophysical methods near Lake Kolon, Hungary. The lake, which is now a protected wetland area with opened water surfaces, was formed in the paleo-channel of the River Danube. Measurements were performed with the help of ground-penetrating radar, the results were calibrated by high spatial resolution drillings. Investigations have been made since 2012, and freshwater limestone was detected at several locations determining the more exact extension of the formation. Ground-penetrating radar proved to be an appropriate method to detect the compact and fragmented freshwater limestone layers in such an environment. However, based on the results the method can be best applied under dry soil or sediment conditions while the uncertainty of the results increases significantly as a matter of higher soil moisture. Further control measurements are necessary verified by several drillings in order to give an exact method to determine freshwater limestone.